Construction and Application of Multimodal Corpus of Chinese Shadow Play - Xiao Zhang; Zhan Yang (Journal of Linguistics and Communication Studies, 2023)
As one of the prominent embodiments of China’s intangible cultural heritage, shadow play embodies the essence and distinctive charm of traditional Chinese culture. This paper aims to provide an overview of the research on Chinese shadow puppetry conducted both domestically and internationally, as well as the current state of database construction pertaining to Chinese shadow puppetry. By reviewing the existing literature and ongoing efforts in multimodal corpus construction within the field, this paper elucidates the significance and process involved in developing a multimodal corpus specifically tailored to Chinese shadow puppetry. Moreover, it highlights the potential applications of this corpus in various domains, including the preservation and transmission of shadow puppetry, the advancement of language application research, the industrialization of cultural resources, and the promotion of traditional culture to a global audience.